EXPLORING THE INTERPLAY BETWEEN CONSCIOUS CONSUMPTION AND IMPULSIVE BUYING: INSIGHTS INTO UNDERSTANDING AND INFLUENCING CONSUMER PSYCHOLOGY (Third Sector Social Economic Review, 2023)
Consumer psychology is a field of study that investigates the psychological factors that influence consumer behaviour and decision-making. Understanding consumer psychology is important for various stakeholders, including marketers, advertisers and policy makers, because it helps to identify the factors that drive consumer behaviour and develop effective strategies to influence and change it. In addition to understanding the psychological factors that influence consumer behaviour, consumer psychology also explores the ways in which consumers process and use information, such as how they evaluate options, make trade-offs and make decisions. This information can be used to design more effective marketing and advertising campaigns and to develop more effective products and services that meet consumers' needs and wants. The need for touch can lead to impulsive buying because people may seek pleasure through the act of purchasing and acquiring material possessions. However, such consumption can often lead to negative consequences such as overspending and financial strain. In contrast, conscious consumption involves being more deliberate and conscious in one's purchasing decisions, considering factors such as need, sustainability, and impact on personal well-being. This study aims to determine the relationship between well-being and need for touch and conscious consumption and their potential effects on unplanned purchasing. For the research, data were collected from a total of 397 people by online survey method using convenience sampling method, which is one of the non-random sampling methods. Frequency distribution, arithmetic mean, measurement model and structural model tests were applied to the data obtained through IBM SPSS and SmartPLS programmes. The results of the study show that psychological factors such as conscious consumption and the need for touch have statistically significant effects on unplanned purchasing. These findings have important implications for understanding consumer behaviour and developing interventions to promote more sustainable and conscious consumption habits.
Keywords: Consumer psychology; Mindful consumption; Need for Touch; Well-being; Impulsive buying